24-hodinové monitorování krevního tlaku u nemocných s esenciální hypertenzí - Siegelová, J; Fiser, B; Dusek, J; Semrád, B; Halberg, F; Cornelissen, G (Vnitrni lekarstvi, 1993)
The aim of the study was to determine the efficiency of enalapril therapy during 24-hours blood pressure monitoring. A group of healthy subjects (C, n = 11), a group of patients with essential hypertension without therapy (EH, n = 9) and a group of patients with essential hypertension II (WHO) treated with enalapril (Acepril Lachema) in once a day doses (13.0 +/- 2.1 mg per kg) during at least 10 months (EH A, n = 8). In all groups of patients and healthy subjects 24-hours blood pressure measurement was provided using Accutracker II equipment. The mean values of systolic (SBP) and diastolic blood pressure (DBP) from 24-hours measurement (+/- SD) were in the group of healthy subjects C 121.38 +/- 10.49/74.79 +/- 7.88 mmHg, in the group EH 146.58 +/- 12.20/88.0 +/- 8.97 mmHg, in the group EH A 127.38 +/- 8.36/74.71 +/- 6.08 mmHg. The differences between the maximum and minimum mean blood pressure values during 24 hours (SBP/DBP) were in the group C 33/27 mmHg, EH 37/29 mmHg, EH A 29/21 mmHg. The smaller difference in SBP and DBP in EH A patients was significant in comparison to C and EH (t-test, p < 0.05). Cosinor analysis proved the results. From our results we can conclude that the Acepril therapy decreases blood pressure more during the day-hours then during night and it is preferable in connection to the risk of night hypotension with hypoxia.
Keywords: Monitoring, Physiologic; Female; monitorování fyziologických funkcí; Humans; ženské pohlaví; Blood Pressure Monitors; monitory krevního tlaku; krevní tlak; enalapril; lidé; mužské pohlaví; hypertenze; lidé středního věku; Blood Pressure; Enalapril; Male; Hypertension; Middle Aged